Partnering dispersion corrections with modern parameter-free double-hybrid density functionals. Issue 21 (9th March 2017) - Sancho-García, J. C.; Brémond, É.; Savarese, M.; Pérez-Jiménez, A. J.; Adamo, C.
Abstract : The PBE-QIDH and SOS1-PBE-QIDH double-hybrid density functionals are merged with a pair of dispersion corrections, namely the pairwise additive D3(BJ) and the non-local correlation functional VV10, leading to the corresponding dispersion-corrected models. Abstract : The PBE-QIDH and SOS1-PBE-QIDH double-hybrid density functionals are merged with a pair of dispersion corrections, namely the pairwise additive D3(BJ) and the non-local correlation functional VV10, leading to the corresponding dispersion-corrected models. The parameters adjusting each of the dispersion corrections to the functionals are obtained by fitting to well-established energy datasets ( e.g. S130) used as a benchmark, giving rise to functionals spanning covalent and non-covalent binding forces. The application of the models to challenging systems out of the training set, like those comprising the L7 database of large supramolecular complexes, or the S66x8 dataset of stretched and elongated intermolecular distances, reveals the high accuracy of the coupling.